Knowledge generation about care‐giving in the UK: a critical review of research paradigms. (13th October 2014) - Milne, Alisoun; Larkin, Mary
Abstract While discourse about care and caring is well developed in the UK, the nature of knowledge generation about care and the research paradigms that underpin it have been subjected to limited critical reflection and analysis. An overarching synthesis of evidence – intended to promote debate and facilitate new understandings – identifies two largely separate bodies of carer‐related research. The first body of work – referred to as Gathering and Evaluating – provides evidence of the extent of care‐giving, who provides care to whom and with what impact; it also focuses on evaluating policy and service efficacy. This type of research tends to dominate public perception about caring, influences the type and extent of policy and support for carers and attracts funding from policy and health‐related sources. However, it also tends to be conceptually and theoretically narrow, has limited engagement with carers' perspectives and adopts an atomistic purview on the care‐giving landscape. The second body of work – Conceptualising and Theorising – explores the conceptual and experiential nature of care and aims to extend thinking and theory about caring. It is concerned with promoting understanding of care as an integral part of human relationships, embedded in the life course, and a product of interdependence and reciprocity. This work conceptualises care as both an activity and a disposition and foregrounds the development of an 'ethic of care', thereby providing a perspective within which to recognise both the challenges care‐giving may present and the significance of care as a normative activity. It tends to be funded from social science sources and, while strong in capturing carers' experiences, has limited policy and service‐related purchase. Much could be gained for citizens, carers and families, and the generation of knowledge advanced, if the two bodies of research were integrated to a greater degree.